Electrophysiology and Radio frequency Ablation - A Novel Method of Treatment in Cardiology - Rajbhandari, Sujeeb (Nepalese Heart Journal, 2006)
Cardiac Electrophysiology and Radiofrequency Ablation (EPS & RFA) is one of the newer modalities of treatment in the field of cardiology. This method of treatmentis directed towards cardiac arrhythmias. Gone are the days when a doctor had to rely on medications to treat such conditions. It's an interventional technique which requires catheters, an EP lab system, cardiac catheterization laboratory and an Electrophysiologist.